Microbial communities in an anaerobic membrane bioreactor (AnMBR) treating domestic wastewater at ambient temperatures in a temperate climate - Penfield, Tyler (Kansas State University, 2017)
The ever-increasing demand for water, food, and energy and the simultaneous diminishment of our planets’ ecosystems wrought by humans have prompted a more sustainable approach to engineering the built environment. Wastewater treatment systems stand at the interface that connects the built and natural environment where potential solutions for resource and environmental issues exist. Wastewater treatment technologies can address issues involving water, food, energy, and environmental regulation when resources are properly captured from the wastewater while it’s being treated. This way of thought allows wastewater to be perceived as a source of valuable products rather than an obligate waste stream. For this reason, anaerobic wastewater treatment is progressively being considered because of its ability to improve energy and resource recovery, while reducing costs and environmental impacts associated with conventional domestic wastewater treatment. More specifically, anaerobic membrane bioreactors (AnMBRs) hold promise to effectively treat wastewater at low temperatures with low energy and nutrient requirements, low sludge production, while having the benefit of generating methane-rich biogas suitable as an energy source and the potential to capture nutrients used to fertilize cropland. But, at low temperatures the microbial communities that control anaerobic digestion (AD) face biochemical obstacles. Elucidating the microbial community dynamics within AnMBRs with respect to seasonal temperatures will give insight on how to efficiently operate AnMBRs with the goal of energy-neutral wastewater treatment. DNA based tools such as advanced high-throughput sequencing was coupled with AnMBR process data to explicate the mechanism of methane production in the suspended biomass of an AnMBR from a mesophilic startup leading into psychrophilic conditions, and then returning to mesophilic temperatures.
Keywords: Environmental engineering; Wastewater treatment; AnMBR; Ambient temperature; Bioreactor; Biotechnology